2022
DOI: 10.3889/oamjms.2022.8115
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of Patients with Musculoskeletal Injury in Children at Tertiary Referral Hospital in Indonesia

Abstract: Introduction: Fractures in children cause a long-term disability and decrease the quality of life in every person involved. Factors that affect fracture incidence must be identified so that we can create prevention management. This study evaluates children's fracture patterns in Saiful Anwar General Hospital Malang from January 2016 until August 2020. Methods: A retrospective study was conducted among children under 18 years old by analyzing patients' medical records.  The characteristics of patients and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 14 publications
1
8
1
Order By: Relevance
“…The average age of the children in this study was 8.15 years for both sexes combined, with a lower average of 7.25 years observed in girls only and a higher one of 8.65 years observed in boys. The combined mean of 8.15 years found in this study is similar to the mean age of 8.78 years reported by Omidiji et al [ 20 ] in a study on fractures in children from Western Nigeria but much lower than the mean of 14 years observed by Sananta et al [ 3 ] in a study from Indonesia. The latter authors, however, studied children between 0 and 17 years as opposed to between 0 and 16 years in this study.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…The average age of the children in this study was 8.15 years for both sexes combined, with a lower average of 7.25 years observed in girls only and a higher one of 8.65 years observed in boys. The combined mean of 8.15 years found in this study is similar to the mean age of 8.78 years reported by Omidiji et al [ 20 ] in a study on fractures in children from Western Nigeria but much lower than the mean of 14 years observed by Sananta et al [ 3 ] in a study from Indonesia. The latter authors, however, studied children between 0 and 17 years as opposed to between 0 and 16 years in this study.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, peak age groups for musculoskeletal injuries in children of 6-12 years and 7-12 years for both sexes have been similarly reported by Song et al [ 21 ] from China and Hussain et al [ 5 ] from India, respectively. In contrast, higher peak periods of 12-18 years and 10 -17 years have been reported by Sananta et al [ 3 ] and Nesje et al [ 2 ] from Indonesia and Norway, respectively. In addition, the modal age of injuries in children of nine years seen in this study is lower than the 16 years observed by Sananta et al [ 3 ].…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations